2018
DOI: 10.3847/1538-3881/aadd9c
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Highly r-process-enhanced Field Stars: Evidence for an Accretion Origin and Detection of Several Groups from Disrupted Satellites

Abstract: We present kinematics of 35 highly r-process-enhanced ([Eu/Fe] ≥ +0.7) metal-poor (−3.8 < [Fe/H] < −1.4) field stars. We calculate six-dimensional positions and velocities, evaluate energies and integrals of motion, and compute orbits for each of these stars using parallaxes and proper motions from the second Gaia data release and published radial velocities. All of these stars have halo kinematics. Most stars (66%) remain in the inner regions of the halo (< 13 kpc), and many (51%) have orbits that pass within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
173
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(193 citation statements)
references
References 133 publications
16
173
4
Order By: Relevance
“…After correcting for the difference in metallicity (0.13 dex), we find a remarkable match between the two stars in the considered range (reduced χ 2 of 0.49). Similarities between the two stars have already been reported in the literature from a kinematical point of view (Roederer et al 2018a) and based on their metallicity (Barklem et al 2005;Roederer et al 2018b). We emphasize, however, that the similarities do not extend to the neutron-capture regime, since HD 222925 is an r-II and HD 20 an r-I star with possible sprocess contamination, as outlined in the following section.…”
Section: Abundances Up To Zn (11 ≤ Z ≤ 30)supporting
confidence: 81%
See 1 more Smart Citation
“…After correcting for the difference in metallicity (0.13 dex), we find a remarkable match between the two stars in the considered range (reduced χ 2 of 0.49). Similarities between the two stars have already been reported in the literature from a kinematical point of view (Roederer et al 2018a) and based on their metallicity (Barklem et al 2005;Roederer et al 2018b). We emphasize, however, that the similarities do not extend to the neutron-capture regime, since HD 222925 is an r-II and HD 20 an r-I star with possible sprocess contamination, as outlined in the following section.…”
Section: Abundances Up To Zn (11 ≤ Z ≤ 30)supporting
confidence: 81%
“…Based on the full 6D phase-space information from the second data release (DR2) of the Gaia mission (Gaia Collaboration et al 2018), Roederer et al (2018a) concluded that HD 20 may be chemodynamically associated with two other metal-poor halo stars with observed r-process excess. Based on its kinematicscharacterized by a highly eccentric orbit (e = 0.975 +0.002 −0.004 ) and a close pericentric passage (r peri = 0.19 +0.04 −0.02 kpc) -and its low metallicity, the authors speculate that HD 20 and its associates may have been accreted from a disrupted satellite.…”
Section: Introductionmentioning
confidence: 99%
“…Surviving UFD galaxies have average densities 1 M pc −3 within their core radii (Simon & Geha 2007), so any UFD-like systems on orbits like that of the Sylgr stream would have disrupted long ago (cf. Roederer et al 2018a). We conclude that the progenitor must have been substantially more dense than the surviving population of UFD galaxies.…”
Section: Light Elements Whose Abundances Vary In Gcsmentioning
confidence: 76%
“…Chemical abundances also show variations between old metal-poor stars in different environments such as dwarf galaxies, suggesting that the first stages of enrichment were not uniform. Stars in the nearby dwarf galaxies typically have lower abundances of αand odd-Z elements, attributed to their slower star formation histories and/or fewer number of high mass stars overall (Venn et al 2004;Tolstoy et al 2009;Nissen & Schuster 2010;McWilliam et al 2013;Frebel & Norris 2015;Hayes et al 2018), while significant variations in heavy r-process elements in some dwarf galaxies, and globular clusters, are discussed in terms of contributions from individual compact binary merger events, like GW170817 (e.g., Roederer 2011;Roederer et al 2018a;Ji et al 2016Ji et al , 2019. In addition, about a third of the [Fe/H] < −2.5 stars 1 in the Galactic halo show very high enhancements in carbon (the carbon-enhanced metal-poor stars, "CEMP"; Yong et al 2013;Aguado et al 2019a also see Kielty et al 2017;Mardini et al 2019), discussed as a signature of the earliest chemical enrichment in the Universe.…”
Section: Introductionmentioning
confidence: 99%